Impact of Quality Improvement Educational Interventions on Documented Adherence to Quality Measures for Adults with Crohn's Disease. Issue 9 (27th May 2015) - Greene, Laurence; Sapir, Tamar; Moreo, Kathleen; Carter, Jeffrey D.; Patel, Barry; Higgins, Peter D. R.
Abstract : Background: In recent years, leading organizations in inflammatory bowel disease (IBD) have developed quality measures for the care of adults with Crohn's disease or ulcerative colitis. We used chart audits to assess the impact of quality improvement educational activities on documented adherence to Physician Quality Reporting System measures for IBD. Methods: Twenty community-based gastroenterologists were recruited to participate in baseline chart audits (n = 200), a series of 4 accredited educational activities with feedback, and follow-up chart audits (n = 200). Trained abstractors reviewed randomly selected charts of adults with moderate or severe Crohn's disease. The charts were retrospectively abstracted for physicians' documented performance of the 2013 Physician Quality Reporting System IBD quality measures. We compared the physicians' baseline and posteducation rates of documented adherence with 10 of these measures. In a secondary analysis, we compared preeducation with posteducation difference scores of low-performing physicians, those whose baseline documentation rates were in the lowest quartile, and the rest of the cohort. Results: At baseline, documentation of mean provider-level adherence to the 10 quality measures ranged from 3% to 98% (grand mean = 35.8%). In the overall analysis, baseline and posteducation rates of documented adherence did not differ significantly for any of the measures. However, for 4 measures, preeducation to posteducation difference scores were significantly greater among low performers than physicians in the highest 3 quartiles. Conclusions: The results of this preliminary pragmatic study indicate that quality improvement education affords the potential to improve adherence to Physician Quality Reporting System quality measures for IBD among low-performing gastroenterologists.